2015
DOI: 10.1074/jbc.m115.656603
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite ATP-independent Periplasmic (TRAP) Transporters Use an Arginine-mediated Selectivity Filter for High Affinity Substrate Binding

Abstract: Background: Haemophilus influenzae requires a substrate-binding protein (SBP)-dependent TRAP transporter to acquire sialic acid.Results: A conserved arginine residue in the SBP is essential for the high affinity and carboxylate specificity of the TRAP transporter.Conclusion: The arginine/carboxylate interaction in TRAP SBPs restricts substrate range to carboxylate-containing substrates.Significance: The study reveals the mechanism by which a key bimolecular interaction underpins bacterial virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…Further structures might reveal whether this is a feature common to the whole family, as suggested by sequence alignments [11]. In addition, the solvation provided by the presence of water molecules may dissipate the charge, as shown previously for TRAP transporters [35]. This repulsive negative charge might, however, be compensated somewhat by the dipoles of helices a1 and a4 and possibly to some extent a5 which are directed towards the carboxylate groups of the substrate.…”
Section: Discussionmentioning
confidence: 68%
“…Further structures might reveal whether this is a feature common to the whole family, as suggested by sequence alignments [11]. In addition, the solvation provided by the presence of water molecules may dissipate the charge, as shown previously for TRAP transporters [35]. This repulsive negative charge might, however, be compensated somewhat by the dipoles of helices a1 and a4 and possibly to some extent a5 which are directed towards the carboxylate groups of the substrate.…”
Section: Discussionmentioning
confidence: 68%
“…Available crystal structures of SBPs indicate that these proteins have individually defined binding sites in which the ligands are coordinated by hydrogen bonds, hydrophobic interactions and one single salt bridge mediated by a highly conserved arginine (M€ uller et al, 2006;Lecher et al, 2009). Recently, Fischer and colleagues showed that the interaction of arginine and the carboxylate restricts the substrate range to carboxylate containing ligands (Fischer et al, 2015). In DctP Am , this arginine residue is located at position 175 in DctP Am and most probably forms a salt bridge with the carboxylic group of D-gluconic acid, D-fuconic acid, D-xylonic acid or D-galactonic acid, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Molecules known to be transported by TRAP transporters range from small organic acids including C4-dicarboxylates, larger sugar acids like N-acetylneuraminic acid (Neu5Ac), to amino acids (4,8). Most TRAP transporter substrates contain a carboxylic acid group, which is specifically recognized by the P domain of the transporter (9).…”
Section: Introductionmentioning
confidence: 99%
“…This residue is crucial for the substrate interaction by recognizing the aforementioned carboxylic acid group in the substrate. It thereby acts as a selectivity filter for the transporter, allowing the SBP to recognize organic acids with high affinity and specificity (9). Thus, P domains are structurally well characterized in their two resting states, namely ''open ligand-free'' and ''closed ligand-bound'', and the interactions between substrate and protein are well studied.…”
Section: Introductionmentioning
confidence: 99%